Pengaruh CR, ROE, ROA, DAR, Dan DER Terhadap Harga Saham Pada Perusahaan Manufaktur Yang Listing Di Bursa Efek Indonesia Tahun 2011-2014 - ANINDITA, NOVITA PUTRI, Drs. Agus Mugorobin, M.M (2017)
This study aimed to determine the effect the Current Ratio, Return on Equity, Return on Assets, Debt To Equity Ratio, and Debt To Total Assets Ratio of stock price. The object of research on manufacturing companies with a sample of 55 companies the period 2011-2014. Data used 55 x 4 at 220. In 198 pengolahnya Final data into the data with SPSS. The analytical tool used using classic assumption test and regression analysis. The results showed that the regression equation HS = 2331.661 + ROE 34,669CR + 187.883 + 842.575 -841.9 ROA- 2224,827DAR DER. At t test showed that the variables CR, ROE, ROA, and DER significant effect on stock prices. DER whereas no significant effect on stock prices. In simultaneous F test CR, ROE, ROA, DAR and DER significant effect on stock prices. For testing determinant coefficient showed that 18.7% of variables CR, ROE, ROA, DAR, and DER is only able to explain the stock price and the remaining 81.3% means that there are other variables that influence it.